Construction of trifluoromethylated quaternary stereocenters via p-quinone methides. Issue 20 (12th February 2020) - Terashima, Kyu; Kawasaki-Takasuka, Tomoko; Agou, Tomohiro; Kubota, Toshio; Yamazaki, Takashi
Abstract : Development of a new synthetic method for the construction of quaternary centers with a CF3 group was realized by way of 1, 6-addition of various nucleophiles to highly reactive δ-trifluoromethylated p -quinone methides generated in situ . Abstract : Development of a new synthetic method for the construction of quaternary centers with a trifluoromethyl group was realized by way of 1, 6-addition of various nucleophiles including active methylene compounds to highly reactive δ-trifluoromethylated p -quinone methides generated in situ from the corresponding tertiary carbonates with a catalytic amount of an appropriate base.